Hubungan Asupan Gizi dan Riwayat Sakit dengan Status Gizi Balita di Wilayah Kerja Puskesmas Feapopi - Margrita Salang; Anna Henny Talahatu; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Nutritional status is a measure of the success of nutrient fulfillment resulting from the balance between nutritional needs and inputs. One of the nutritional problems is undernutrition that occurs due to an imbalance between the consumption and absorption of nutrients and their use in the body¹. This type of research is quantitative with a cross-sectional study design with a sample of 75 out of 344 children aged 1-3 years in the working area of the Feapopi Health Center. Data analysis uses the chi square test with the SPSS application. Based on the results of the analysis, it can be concluded that 1. There was no relationship between knowledge and nutritional intake (energy and protein), namely (p=0.317, p=0.343). 2. There is a relationship between the number of family members and nutritional intake (energy and protein), which is (p=0.001) 3. There was a relationship between family expenditure and nutritional intake (energy and protein) (p=0.063, p=0.062) 4. There was a significant relationship between infectious diseases and the nutritional status of BB/U (p=0.001) and BB/TB(p=0.002) 5. There was a significant relationship between nutritional intake (energy and protein) and the nutritional status of BB/U (P=0.001, P=0.002) and BB/TB (p=0.001, P=0.001) 6. There is a relationship between nutritional intake (energy and protein) and infectious diseases on nutritional status.